Gambaran Penanganan Ibu Hamil Dan Bersalin Pada Suku Boti Dalam Kecamatan Kie Kabupaten Timor Tengah Selatan - Joy January A. S. Ninu; Slamet Rihadi; Kusuma Tirtahusada (JURNAL WIDYA MEDIKA, 2018)
Maternal Mortality Rate (MMR) and Infant MortalityRate (IMR) in ASEAN are high, including Indonesia. An analysis by the Directorate of Maternal Health in 2010 indicates that maternal mortality is closely related to a helper and place or delivery facility. This research uses qualitative method with ethnography research type. The research was conducted at Boti Tribe of KiE Subdistrict of South Central Timor District (TTS) of East Nusa Tenggara Province (NTT) with research focus in Boti Dalam Tribe. The results showed that the main factor that makes the community of Tribe Boti Dalam tends to use the help of maternity dukun is the belief and adherence to following the adat. In the treatment of pregnant women and maternity, traditional birth attendants still use traditional methods ranging from massage andvarious traditional ingredients that are believed to improve maternal health conditions and overcome various complications that arise during pregnancy, childbirth, and childbirth and post partum.. The equipments are still traditional. The researcher suggested that regeneration and training of maternity dukun on the procedures for the handling of pregnant women and healthy and safe maternal mothers should be provided to the Boti Dalam tribecommunity with socio-cultural approach and local policy